Room temperature CO gas sensing using Zn-doped In2O3 single nanowire field effect transistors - Singh, Nandan (2013)
We demonstrate a room temperature sensing of CO gas (1–5 ppm) using high performance single Zn-doped In2O3 nanowire field effect transistors (Zn–In2O3 NW-FETs). Zn–In2O3 nanowires were grown in a horizontal CVD furnace; single Zn–In2O3 NW-FETs were fabricated using SiNx dielectric layer and bottom gate. Electrical measurements on the NW-FETs showed high performance devices, with a high “ON” current of 8 × 10−6 A at a 5 V drain voltage, high on-off ratio of ∼106 and electron mobility of 139 cm2 V−1 s−1. Sensing properties of CO gas were studied using these NW-FETs at room temperature. Doping of Zn2+ into the In2O3 NW enhances the sensor response compared to pure In2O3 nanowire. A good selectivity of CO gas over NO and NO2 can also be achieved. The improved sensor response at room temperature is attributed to the defects created and a change in conductivity of the nanowire upon Zn-doping. Significant negative threshold voltage shift of −3.5 V was observed after exposure to a low concentration of CO gas at 5 ppm. This approach represents an important step towards the room temperature sensing of hazardous gas.